Ibnu Miskawaih's Islamic Economic Thinking (Reviewing The Concept of Exchange and The Role of Money According to Ibnu Miskawaih) - Sri Noor Mustaqimatul Hidayah (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to examine the concept of exchange and the role of money according to Ibnu Miskawaih. This research on the concept of exchange and the role of money is carried out by using a library research approach, namely, by recording all findings and combining all findings, both theories or new findings from books, websites, articles and newspapers on the study of the concept of exchange and the role money according to Ibn Miskawaih. The results of the study show that Ibn Miskawayh's Islamic Economics thought a lot about the exchange of goods and services and the role of money. According to him, humans are social beings who need each other to meet the needs of goods and services. Therefore, humans will exchange goods and services with appropriate compensation (riward, al-mukafad al-munasibah). Humans act as assessors and balancers (al-muqawwim al-musawwi baynahuma) in exchange so as to create justice. Ibn Miskawaih also discussed the advantages of gold coins (dinar) which are widely accepted and become substitutes (mu'awwid) for all types of goods and services. This is because gold is a metal that is durable, easy to carry, not easy to imitate, desired and loved by many people